Transitional adakite-like to calc-alkaline magmas in a continental extensional setting at La Paz Au-Cu skarn deposits, Mesa Central, Mexico: metallogenic implications - Porfirio J. Pinto-Linares; Gilles Levresse; Jordi Tritlla; Víctor A. Valencia; José M. Torres-Aguilera; Manuel González; David Estrada (Revista Mexicana de Ciencias Geológicas)
The granodiorite intrusions with associated Cu-Au skarn mineralization of La Paz district are located in the east part of the Mesa Central of Mexico. The skarn developed at the contact between a middle Cretaceous calc-argillaceous sedimentary sequence and the magmatic intrusions. A Ag-Pb-Zn vein system postdates the intrusive-skarn assemblage. Two well defined fault systems (N-S and E-W) divide the La Paz district. The N-S Dolores fault, with a normal vertical displacement estimated between 500 to 1000 m, separates the western Au-Cu skarn zone from the eastern hydrothermal Ag-Pb-Zn vein system. This fault is considered to be part of the Taxco-San Miguel de Allende fault system. The U-Pb dating of the intrusives at the La Paz district clearly indicates a single emplacement event dated at ca. 37 Ma (monocrystal zircon age). This age probably represents the last post-Laramide orogenic mineralizing event known to occur in the Sierra de Catorce district. Also, four calculated discordant ages suggest the presence of greenvilian basement underneath a a thick crust (35-45 km).